2015
DOI: 10.3892/mmr.2015.4176
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 protects bone marrow-derived mesenchymal stem cells against serum deprivation-induced apoptosis

Abstract: Mesenchymal stem cells (MSCs) have become a recent focus of experimental and clinical research regarding myocardial regeneration. However, the therapeutic potential of these cells is limited by poor survival. Prostaglandin E1 (PGE1) is known to have anti-inflammatory and anti-apoptotic effects on the myocardium. The aim of the present study was to determine whether PGE1 could protect MSCs against serum deprivation (SD)-induced apoptosis. An SD model was used to induce apoptosis in MSCs in vitro. Apoptotic morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…It was shown that treatment with MSCs and PGE1 in rats significantly reduced apoptosis induced by serum deprivation, decreased the protein levels of Bax and caspase-3, and increased that of Bcl-2; however, the underlying mechanism remained unclear [ 28 ]. Prostaglandin E2 (PGE2) can increase HIF-1α expression in hematopoietic stem/progenitor cells (HSPCs), thereby increasing CXCR4 expression and promoting the homing of HSPCs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that treatment with MSCs and PGE1 in rats significantly reduced apoptosis induced by serum deprivation, decreased the protein levels of Bax and caspase-3, and increased that of Bcl-2; however, the underlying mechanism remained unclear [ 28 ]. Prostaglandin E2 (PGE2) can increase HIF-1α expression in hematopoietic stem/progenitor cells (HSPCs), thereby increasing CXCR4 expression and promoting the homing of HSPCs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…BM-MSCs have been shown to degrade functionally and quantitatively with increase in age of patients undergoing successful reperfusion treatment, and hence this aspect of the MSCs needs to be explored further [ 95 ]. Prostaglandin E 1 protects BM-MSCs against serum-deprived induced apoptosis by decreasing Bax and caspase-3 expression levels and increasing Bcl-2 expression [ 96 ]. In one study, bone marrow cells derived from heart failure patients were shown to express higher levels of remodelling enzymes and pathways regulating tissue remodelling, scar formation and maturation.…”
Section: Main Textmentioning
confidence: 99%
“…One available strategy to enhance MSC survival is treatment with agents that can enhance the viability of MSCs. For example, a previous study reported that prostaglandin E improved MSC survival under H/SD conditions, which is a commonly used model to mimic the ischemic environment in vitro (18). Another study reported that nicorandil protected MSCs from H/SD-induced apoptosis (19).…”
Section: Discussionmentioning
confidence: 99%